Catholic education in Lithuania: an alternative for the dominating education system? - Voidogaitė, Viktorija (Journal of Education Culture and Society, 2022)
In this article it is discussed whether the catholic education may be approached as the alternative for the dominating education system. In the theoretic part I did reveal that regarding to the historical context, the catholic education is a traditional, during different periods reflourishing phenomenon. That is why the notion alternative while speaking about a catholic school in Lithuania may be used in some extremely specific cases: a) how catholic education becomes an opposition for different repressions as well as for a worldview that is uncongenial for the catholic culture; b) when there is an objective to gain reservations necessary for an education institution as well as not to pursue certain reforms that are provided for at a national level.Phenomenological analysis has grasped that an incredibly special space of a catholic school that appears in the remembrance of the participants of the analysis, is a chapel. A relation based on trust between adults and pupils in a catholic school, stimulates pupils to proceed the same well that they witness the senior (teachers and other pupils) as well as their peers (building team and embracing correlation) doing. On the other hand, negation and disregard of a classroom relation problems may lead to hidden, decennial sneering. Body dimension at a catholic school displays in several aspects: voluntary physical assistance and embracing look at the different one, a shocking collision with a theme about one’s sexuality and peaceful belief in body resurrection that provides strength and hope. Exclusive time in catholic education – planned retreat kairos time. Other scheduled liturgical practice (Mass) for some pupils becomes as resistance time for senselessness. Also, the transformation time when worldview of a school is changing, leads to foreignness and anxiety experience that stimulates resistance as well as desire to replace a school back to the usual, “normalcy” condition.Some exceptional catholic education features that are mentioned in a theoretic part of the article also are seen in findings of phenomenological analysis, that are: pastoral care practices, liturgical practices and practise of mercy activities.